A more effective catalysis of the CO2 fixation with aziridines: computational screening of metal-substituted HKUST-1. Issue 14 (16th June 2021) - Jiang, Yan; Hu, Tian-ding; Yu, Li-ying; Ding, Yi-hong
Abstract : By performing the first computational screening on the cycloaddition of CO2 with aziridines under 18 metal-substituted HKUST-1 MOFs and TBAB as a co-catalyst, up to 11 M-HKUST-1 systems possess superior catalytic ability to the original Cu-HKUST-1. Abstract : A vital issue for the fixation and conversion of CO2 into useful chemical products is to find effective catalysts. In this work, in order to develop more effective and diverse catalysts, we implemented the first computational screening study (at M06-2X//B3LYP level) on the cycloaddition of CO2 with aziridines under eighteen metal-substituted HKUST-1 MOFs and tetrabutylammonium bromide (TBAB) as a co-catalyst. For all considered catalytic systems, the ring-opening of aziridine is calculated to be the rate-determining step. Up to 11 M-HKUST-1 systems, i.e., Rh (31.87 kcal mol −1 ), Y (31.02), Sc (30.50), V (30.02), Tc (29.90), Cd (29.80), Ti (29.32), Mn (29.05), Zn (28.29), Fe (27.85) and Zr (25.09), possess lower ring-opening barrier heights than the original Cu-HKUST-1 (32.90), indicative of their superior catalytic ability to the original Cu-HKUST-1 in theory. With the lowest ring-opening barrier, Zr-HKUST-1 is strongly advocated for future synthetic and catalytic studies.